Performance consulting a strategic process to improve, measure, and sustain organizational results - Robinson, Dana Gaines 1944- (Berrett-Koehler Publishers, 2015)
This third edition of the classic book that introduced performance consulting adds a wealth of new material. There are new case examples throughout and four new chapters providing detailed steps for measuring results from performance consulting initiatives on five different levels, including ROI. The book includes a never-before-published Alignment and Measurement Model, allowing you to connect organizational needs and performance consulting initiatives designed to address those needs with the appropriate level of measurement. It features tools, models, and checklists and will enable you to make a difference in your organization that is valued, measurable, and sustainable. --
Includes bibliographical references and index. - Print version record
Keywords: Business consultants -- Training of; Performance; Performance technology; Task Performance and Analysis; Rendement au travail; BUSINESS & ECONOMICS; Industrial Management; BUSINESS & ECONOMICS; Management; BUSINESS & ECONOMICS; Management Science; BUSINESS & ECONOMICS; Organizational Behavior; Business consultants; Training of